అణు వర్ణపట విజ్ఞానం ప్రాథమికాంశాలు - Colin N. Banwell; Elaine M. Mccash (My University, 2019)
The book deals with the interaction of electromagnetic waves and matter. It remains an elementary and non-mathematical introduction to molecular spectroscopy that emphasizes the overall unity of the subject and offers a pictorial perception rather than a mathematical description of the principles of spectroscopy. The examples cited in the book are based on modern instruments.
Fundamentals of Molecular Spectroscopy
Keywords: Telugu